2000
DOI: 10.1210/jcem.85.4.6553
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of the Novel Thyroid and Eye Muscle Shared Protein G2s: Autoantibodies against G2s Are Closely Associated with Ophthalmopathy in Patients with Graves’ Hyperthyroidism

Abstract: Serum autoantibodies against eye muscle antigens are closely linked with thyroid-associated ophthalmopathy (TAO), although their significance is unclear. The two antigens that are most often recognized are eye muscle membrane proteins with molecular masses of 55 and 64 kDa, as determined from immunoblotting with crude human or porcine eye muscle membranes. We cloned a fragment of the 55-kDa protein by screening an eye muscle expression library with affinity-purified anti-55 kDa protein antibody prepared from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Recently, it has been shown that the appearance of FpAb in Graves' patients during methimazole therapy, accurately predicts the development of ophthalmopathy with EM impairment, while the presence of G2sAb predicts the onset of ophthalmopathy with both EM involvement and retroorbital connective inflammation (Gunji et al ., 1999(Gunji et al ., , 2000Kaspar et al ., 2002). Finally, high extraocular muscle antibody levels have been also found in patients with euthyroid Graves' ophthalmopathy (Perros & Kendall-Taylor, 1992;Amato et al ., 2000).…”
Section: Measurements Emab Were Evaluated In All Samples By Indirect mentioning
confidence: 93%
See 2 more Smart Citations
“…Recently, it has been shown that the appearance of FpAb in Graves' patients during methimazole therapy, accurately predicts the development of ophthalmopathy with EM impairment, while the presence of G2sAb predicts the onset of ophthalmopathy with both EM involvement and retroorbital connective inflammation (Gunji et al ., 1999(Gunji et al ., , 2000Kaspar et al ., 2002). Finally, high extraocular muscle antibody levels have been also found in patients with euthyroid Graves' ophthalmopathy (Perros & Kendall-Taylor, 1992;Amato et al ., 2000).…”
Section: Measurements Emab Were Evaluated In All Samples By Indirect mentioning
confidence: 93%
“…One of the main antigens associated with eye muscle damage is a new thyroid and eye muscle shared protein of unknown function, called G2s. It is a cell-membrane protein, with a molecular mass of 55 kDa (Gunji et al ., 2000). Moreover, another antigen has been recently identified; it is a flavoprotein (Fp) subunit of mitocondrial succinate Correspondence: Annamaria De Bellis, MD, Chair of Endocrinology, Second University of Naples, via Pansini N. 5, 80131 Naples, Italy.…”
Section: Measurements Emab Were Evaluated In All Samples By Indirect mentioning
confidence: 99%
See 1 more Smart Citation
“…29 The extraocular muscles and thyroid share antigens with clinical relevance in TAO, such as calsequestrin, G2s, 19 and UACA 21 antigens. In this study, we observed a close relationship between positive reactivity of serum calsequestrin antibodies (87.9%) and active TAO, which corroborates previous report.…”
Section: Discussionmentioning
confidence: 99%
“…18 G2s, the terminal 141 amino-acid fragment of the winged-helix transcription factor FOXP1, were found both in the extraocular muscles and thyroid, but not in orbital connective or adipose tissue. 19 Anti-G2s antibodies were also reported to be associated with active ophthalmopathy in the patients with Graves's hyperthyroidism, being detected in 54% of patients with active TAO compared to 33% of those with inactive disease. 20 UACA is an auto-antigen associated with panuveitis, and is expressed in eye muscle as well as human thyroid follicular cells.…”
Section: Introductionmentioning
confidence: 98%